Vozes silenciadas: as mulheres da geração beat - (:unkn) unknown (Universidade Federal de Goiás, 2018)
This research looks for to extend the knowledge on the history of the women, being taken as base and example the history of the women beats. Before going into in the history of the women who had been part of this generation, we made an analysis on the contracultural movement Beat generation, the historical context of the period and, after these considerations, we ponder of that forms the women were inserted inside of the circle. As research source, we use the autobiográfico book of the writer beat Carolyn Cassady -, My Years With Cassady, Kerouac and Ginsberg -, to be able to understand as it inserted itself in the movement and as the men beats, exactly that involuntarily, they strengthened the sort papers. At the same time, we search to analyze the United States society of the second half of century XX, to be able to understand which they had been the places denied to the women and of that forms the relations of being able and the imaginary one on the place of each one had been being constituted. We lead in consideration, also, the difficulties in if studying the women in history. For the analyses that in we consider them to make, it is important to evaluate as the society dealt with these women, which was the relations of being able that already they permeavam the society and of which forms these relations (reverse speed) were constructed and strengthened daily. As cloth of deep, we take in consideration the history of the women and the deletion of these personages in our history, memory and in our books, that is, of that it forms these absences in /de the historical sources daily are reflected in the didactic materials and taught History/learned. We look for to extend the notion of the importance of the women in history and memory, not leaving that the silence and the deletion of its lives and histories hinder its appearance in the historical knowledge and the History taught in classrooms.
Keywords: Geração beat; História das mulheres; Relações de poder; Autobiografia; Beat generation; History of women; Power relations; Autobiography; HISTORIA::HISTORIA MODERNA E CONTEMPORANEA